Use of alkali-activated palm oil fuel ash reinforced by microfibres for soft soil stabilisation - Pourakbar, Shahram (2015)
The construction of heavy structures on soft soils in tropical regions is a high challenging task. The soft soils are generally characterized by low undrained shear strength and poor bearing capacity. Deep mixing is one of the beneficial soil improvement techniques that could be applied successfully to overcome these problems by improving geotechnical characteristics of soils with cement and other traditional cementitious binders. Although such hemical binders can improve many engineering properties of soils, they have several shortcomings. The primary motivation for this study was to investigate the innovative reuse of a locally available by-product to eliminate traditional binders from deep mixing projects. In this respect, the use of palm oil fuel ash (POFA) as a well-known agricultural waste deserves a special attention. This research consists of four main stages. The first stage is the performance of the preliminary investigation in order to evaluate the effectiveness of POFA (individually and in combination with cement) on some basic geotechnical characteristics of soft soil. The unconfined compression strength(UCS) was used as a practical indicator to investigate the strength development.According to the test results, combining POFA with cement results in a sharp increase in the UCS of the samples, whereas in the same curing time, the strength development of POFA-stabilized soil was not remarkable. In the second stage of this research, alkaline activation of POFA was adopted as a viable technique to fully eliminate cementitious binders from geotechnical applications. In simple words, alkali-activated binder is generally a synthetic alkali aluminosilicate which is produced from the reaction of a solid aluminosilicate with pre-designed concentrated aqueous alkaline solutes. Based on the obtained UCS values at curing periods of up to 6 months, using alkali-activated POFA increased the peak strength of soil by up to 70 times compared to that of natural soil. Beside the shear strength development, in order to increase the tensile strength and ductility of treated soil, the combined effect of fibre inclusion and alkaline activation is described and reported in the third stage. In this stage, along with the POFA in presence of high alkali solutes, mineral wollastonite microfibres (CaSiO3) were used as a strong reinforcement inclusion. Beside the UCS test, indirect tensile strength and flexural strength tests were carried out at curing periods of up to 6 months. The test results indicated that the inclusion of fibre reinforcement within alkali-activated POFA, caused a further increase in the peak stress and tensile strength, and decreased the loss of post-peak strength. In the last stage of this research, a geotechnical design procedure of interaction between a strip footing and stabilized soil is modelled in the laboratory using the column technique. This part takes into account the geotechnical characteristics of the stabilized soil columns and simulates fairly well the coupled effect of alkali-activated POFA and reinforcement inclusion (APR) in deep mixing projects. The test results demonstrated the strong contribution of APR to the soil matrix, which led to a sharp increase in the bearing capacity of up to 204% in the treated soil columns.